Crimea : la primera gran guerra - Figes, Orlando; Rosenberg, Mirta, 1951-; Figes, Orlando (Barcelona, España ; Capital Federal, Buenos Aires, Argentina : Edhasa, 2012)
From "the great storyteller of modern Russian historians" comes the definitive account of the Crimean War, a forgotten war that shaped the modern age. Figes reconstructs the first full conflagration of modernity, a global industrialized struggle fought with unusual ferocity and incompetence.
Guerras religiosas -- Cuestiones orientales -- La amenaza rusa -- El fin de la paz en Europa -- La guerra falsa -- Los turcos se llevan el primer triunfo -- Alma -- Sebastopol en otoño -- Los generales Enero y Febrero -- Carne de cañón -- La caída de Sebastopol -- París y el nuevo orden -- Epílogo: La guerra de Crimea en el mito y la memoria.
Published in ePub format in 2013.
Online resource; title from PDF title page (Digitalia, viewed September 4, 2015)
Keywords: Crimean War, 1853-1856.; Electronic books